Shelf-Life Measurement of Dried Fish (Keumamah) using The Accelerated Shelf-Life Testing (ASLT) with The Arrhenius Model using Microwave - Ismail Sulaiman; Ismail Sulaiman; Ismail Sulaiman; Ikhsanul Khairi (Universitas Darussalam Gontor, 2024)
Indonesia is one of the archipelagic countries with unlimited potential for fish resources, this is evidenced by the extent of Indonesia's marine waters reaching 295,370 km, stretching from the Indian Ocean to the Atlantic Ocean. The large amount of fish, especially in certain periods, makes the price of fish cheap. Therefore, the fish needs to be processed to produce a more diverse product diversification, one of which is wood fish which is a typical Acehnese food known as keumamah fish. This keumamah fishcan be processed by drying and has a long shelf life, but if improper handling in processing and storage causes this product to spoil quickly. This study was conducted to look at storage methods with pretreatment so that keumamah fish can be stored longeras measured by the Accelerate Self Life Testing Method with the Arrhenius model. This study was conducted by drying the fish (Thunnus)with preliminary treatment using50 hertzmicrowavewave(5 and 7 minutes) and storing the fish packaged using polyethylene plastic in an oven with temperatures of 35, 45 and 550C and analyzing the critical point on moisture content and microbial count during the storage process. The results of the analysis show that the shelf life of wood fish with 7 minutes of microwave pretreatment and oven drying at 55 0C, the fish can be stored in the ovenuntil 120 days.